2022
DOI: 10.1021/acs.joc.2c00151
|View full text |Cite
|
Sign up to set email alerts
|

N-Aminoacyl-3-amino-nido-carboranes as a Group of Boron-Containing Derivatives of Natural Amino Acids

Abstract: Figure 1. Main concepts of carboranyl amino acid derivatives. Note pubs.acs.org/joc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Earlier, it was shown that the decapitation of 3-bromo-and 3-iodo-ortho-carboranes proceeds with the retention of the substituent [56]. The retention of a substituent is also characteristic of 3-alkyl-, 3-aryl-, and 3-alkynyl-orthocarboranes [53,[57][58][59][60], as well as of 3-amino-ortho-carborane and other derivatives with a B-N bond [61][62][63][64][65]. At the same time, decapitation of 3-fluoro [66] and 3-hydroxy [67] derivatives of ortho-carborane leads to mixtures of the parent nido-carborane and the corresponding substituted nido-carboranes, i.e., is not selective.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, it was shown that the decapitation of 3-bromo-and 3-iodo-ortho-carboranes proceeds with the retention of the substituent [56]. The retention of a substituent is also characteristic of 3-alkyl-, 3-aryl-, and 3-alkynyl-orthocarboranes [53,[57][58][59][60], as well as of 3-amino-ortho-carborane and other derivatives with a B-N bond [61][62][63][64][65]. At the same time, decapitation of 3-fluoro [66] and 3-hydroxy [67] derivatives of ortho-carborane leads to mixtures of the parent nido-carborane and the corresponding substituted nido-carboranes, i.e., is not selective.…”
Section: Resultsmentioning
confidence: 99%
“… 44 While no cytotoxic impact was seen in cells that had been exposed to BPA, a modest cytotoxic effect was noted in cells treated with different concentrations of 13 (from 1 to 1 mM) as well as an enhanced cell‐killing effect 13 ‐treated cells when irradiated with thermal neutrons 44 . Gruzdev et al managed to synthesize the nido ‐carboranyl derivatives of natural (S)‐amino acids 14 , 45 successfully varying side chains, including water‐soluble amino acids that were used as a basis for the synthesis of organoboron peptide‐based compounds.…”
Section: Debut Of the New Boron Agent Developed For Bnctmentioning
confidence: 99%
“…In this regard, the development of synthetic approaches to new carboranyl derivatives of amino acids is of considerable interest. Previously, we have obtained a series of carboranyl derivatives of natural amino acids containing a 3-amino- closo - o -carborane residue as well as planar-chiral closo - and nido -carborane-based amino acids …”
Section: Introductionmentioning
confidence: 99%